The Science of Siren Songs Stradivari unveiled : A Conversation with Joseph Curtin. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and master violinmaker and acoustician Joseph Curtin, recipient of a MacArthur Fellowship. This in-depth conversation explores Curtin's long quest to characterize the sound of a Stradivari violin and the rigorous series of double-blind tests he and his colleagues developed to probe whether or not professional musicians can really tell the difference between a Stradivari and a modern violin. The conversation also covers violin acoustics and how Joseph Curtin marries acoustic science to the art of violin making and merge.